Retrospective analysis of disease characteristics and treatment patterns among patients with esophageal cancer across 14 surgically represented centers - Zhihao Lu; Mingfei Geng; Yongtao Han; Jianzhong Cao; Jun Wang; Tianshu Liu; Xianglin Yuan; Xue Meng; Yanqiao Zhang; Rong Zhao; Lixin Wan; Enxiao Li; et al. (Cancer Biology & Medicine)
Objective: Esophageal cancer (EC) ranks eighth among cancers in cancer-related deaths globally, and ~44% of new cases occur in China. We sought to describe the clinical characteristics and treatment landscape of EC in China before the approval of immunotherapy in 2020. Methods: CHANNEL was a large, retrospective study using patient-level data from 14 hospitals/cancer centers across China, including adults initiating therapy for newly diagnosed EC (January to December 2018). Demographics, clinicopathologic characteristics, and treatment patterns over 6 months were descriptively summarized. Results: Of 3,493 patients, 75.7% were men, the mean age was 64.1 years, and 75.0% had no family history of cancer. Most (92.8%) had squamous cell carcinoma, with a primary lesion in the middle esophagus (56.4%). Among patients with resectable EC, 92.9% received initial surgery, and 7.1% received neoadjuvant therapy, primarily chemotherapy (85.5% platinum-taxane). Among patients with unresectable early or locally advanced EC, 50.8% and 49.2% received palliative and radical therapy, respectively, as the initial treatment, primarily chemotherapy (66.5% platinum-taxane) and chemoradiotherapy (50.8% platinum-taxane), respectively. Adjuvant therapy was administered to 22.9% of patients undergoing initial surgery, and 2.4% receiving neoadjuvant therapy and surgery. Among patients with advanced EC, 84.6% received systemic therapy as an initial treatment, primarily chemotherapy (61.5% platinum-taxane). Conclusions: Before the approval of immunotherapy in China, most patients with resectable early or locally advanced EC underwent radical surgery without preoperative treatment, whereas most patients with advanced EC received platinum-taxane chemotherapy. These findings highlight the need for novel EC treatments before immunotherapy was introduced, and provide a baseline for evaluating the benefits of immunotherapy, now that this treatment is widely used in this setting.